Peran Kelembagaan Kantor Wilayah Kementerian Hukum dan HAM Dalam Upaya Optimalisasi Fungsi Lembaga Pemasyarakatan - Simamora, Janpatar; Pardede, Putri Desima (Nagari Law Review, 2024)
The aim of this research is to find out more about the institutional role of the Regional Office of the Ministry of Law and Human Rights in efforts to optimize the performance and implementation of the main functions of correctional institutions. As is known, over time, the growth rate of inmates in correctional institutions is getting higher and higher. Meanwhile, on the other hand, it is highly hoped that correctional institutions can develop all prisoners to become complete individuals, realize their mistakes, improve themselves, and avoid criminal behavior in the future. In the end, prisoners are expected to be able to reintegrate into society, actively contribute to development and live a law-abiding life. This research methodology uses a normative approach by examining a number of related documents and legal regulations. Data is collected through library research to search for publications and other relevant materials related to the research topic, so as to increase the accuracy of the research materials collected. Of course, it is highly hoped that the institutions of the Regional Office of the Ministry of Law and Human Rights in each region can carry out optimal performance by fully supporting the implementation of the functions and duties of Correctional Institutions through developing the personality and independence of inmates, including the development of religious, national and state awareness, intellectual capacity, legal awareness, healthy reintegration into society, and physical and mental health. The work service activity program needs to be offered and built from the start through a pattern of developing independence through providing work skills based on groups and talents identified while the prisoner is in a correctional institution.